Wiedza w rozwoju przedsiębiorczości w małym warsztacie samochodowym - Włodarczyk, Mirosław; Janczewski, Jerzy (Przedsiębiorczość - Edukacja, 2008)
Growing number of second hand cars imported to Poland caused fast development of theautomotive services occurring mainly in the small enterprises. New knowledge and advancedtechnical equipment were required for satisfactory level of service. The main factors causing theneed of change in the behavior and activity of entrepreneurs have been discussed here.